A Successful Collagenase and Hyaluronic Acid Topical Use Combined with Antibiotic Therapy in the Treatment of Ulcerative Lesions Arising on Tattoo - Paolo Fioramonti; Pasquale Fino; Martina Ruggieri; Nicolò Scuderi; Maria Giuseppina Onesti (Case Reports in Medicine)
Tattooing is an ancient art widely practiced allover the world. The procedure used in making a tattoo consists of puncturing the dermis and depositing an amount of ink, but this decorative technique is not devoid of potential adverse effects, such as infectious complications, hypersensitivity reactions to pigments (lichenoid and granulomatous reactions), the development of benign or malignant tumors, and chronic dermatoses on site of the tattoo. We report an unusual complication which arose on a colorful tattoo and the innovative use of collagenase (Bionect Start) to treat it. With conservative treatment and the use of Bionect Start, we obtained complete resolution and reepithelialization of the lesions, in addition to perfect preservation of the colors of the tattoo.